Μελέτη πολυφαινόλων και αντιξειοδωτικής ικανότητας σοκολάτας - Σιάντωνα, Αναστασία (Department of Agricultural Sciences, Biotechnology and Food Sciences, Cyprus University of Technology, 2013)
Recent studies have shown that dark chocolate could be regarded as functional food. This occurred due to its antioxidant capacity and its very high content of phenolic compounds. Chocolate’s properties are owed to its cocoa content, which is an excellent source of antioxidants and the main raw material for its preparation. Polyphenols in chocolate are distinguished in proanthocyanidins (58%), the flavanones-3-ols (37%) and anthocyanins (4%). The aim of this study was to (a) develop a suitable method for extracting polyphenols from chocolate, (b) to study the effects of storage period in phenolic content and antioxidant capacity of chocolate and finally, (c) to compare between seven randomly selected chocolates (≥ 56% cocoa) from the market and 4 different types of chocolate (A: normal chocolate, B: high flavanol chocolate, C: high flavanol chocolate with royal jelly added at 39°C and D: high flavanol chocolate with royal jelly added at 48,5 ° C), from a local producer ("The Platres Chocolate Workshop", John Adams), who claims that his own chocolate products contain three times more flavanols than any other typical dark chocolate. To optimize the extraction method, samples of high flavanol chocolate underwent three methods of extraction namely (a) ultrasonic extraction (30 °C/30 min), (b) conventional solid–liquid extraction (50°C/30 min) and (c) extraction by Soxtec. For each extraction three solvents were used 70% acetone, 70% methanol and 70% ethanol. Subsequently, chocolate extracts were analyzed for their antioxidant capacity by the FRAP method and their content of total phenolics and flavonols, by Folin-Ciocalteu and the vanillin assay, respectively. To study the effect of storage in phenolic content and antioxidant capacity of chocolates, chocolate samples (A-D) were kept at 18°C for 40 days. During that period seven samples were collected i.e. 1st, 3rd, 10th, 15th, 22nd, 30th, 40th day. Chocolates were extracted by the selected methodology and were analyzed for their antioxidant capacity by FRAP and DPPH methods and their content of total phenolics and flavonols by Folin-Ciocalteu and the vanillin assay, respectively. Finally, the comparison between different types of chocolate was based on the variance analysis (One-way ANOVA) in accordance to Duncan test (P ≤ 0.05).
Keywords: Chocolate; Phenolic compounds